2013
DOI: 10.1002/bdra.23212
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Basis of Congenital Upper Limb Anomalies: Analysis of 487 Cases of a Specialized Clinic

Abstract: The two etiologies differ in terms of patient's clinical features, morphology defect and axis involvement. This data may be helpful to the clinician during the patient's diagnostic workup by indicating the necessity for genetic testing and for determining the anomaly's recurrence risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 20 publications
(20 reference statements)
0
12
0
Order By: Relevance
“…There are large numbers of known single gene mutations listed either by name or number in MIM. Some detailed genetic studies of limb defects have been done by others; for example, Carli et al () in a retrospective review of 487 cases of congenital anomalies involving the upper limb, found a genetic etiology in 41% ( n = 199) and non‐genetic in the remainder ( n = 288); 13 with confirmed chromosome abnormalities and 186 ascribed to a single gene causation, but only 23 confirmed by testing. Their non‐Mendelian list included 26 cases of VACTERL and 15 with unilateral isolated thumb and all the radial aplasias were in the Mendelian group.…”
Section: Discussionmentioning
confidence: 99%
“…There are large numbers of known single gene mutations listed either by name or number in MIM. Some detailed genetic studies of limb defects have been done by others; for example, Carli et al () in a retrospective review of 487 cases of congenital anomalies involving the upper limb, found a genetic etiology in 41% ( n = 199) and non‐genetic in the remainder ( n = 288); 13 with confirmed chromosome abnormalities and 186 ascribed to a single gene causation, but only 23 confirmed by testing. Their non‐Mendelian list included 26 cases of VACTERL and 15 with unilateral isolated thumb and all the radial aplasias were in the Mendelian group.…”
Section: Discussionmentioning
confidence: 99%
“…However, the exact incidence of non-syndromic thumb hypoplasia is difficult to determine, since the isolated malformation does not differ from syndromic cases that in older studies might have gone undetected. In a recent report from a multidisciplinary group on upper limb anomalies, isolated thumb hypoplasia was found in 24/487 cases (4,9%); moreover, in 9 of those the anomaly was bilateral (1,8% of the total and 37.5% of the thumb anomalies) [ 6 ]. In other studies, the bilateral involvement is reported in about 60% of the affected patients, but when unilateral, the right hand is more commonly affected [ 50 , 51 ].…”
Section: Sporadic Formsmentioning
confidence: 99%
“…Radial deficiencies (RDs) are defined as any degree of congenital hypo/aplasia of thumb, thenar muscles, first metacarpal bone, radial carpal bones (scaphoid and trapezium) and/or radius, occurring with a live birth incidence ranging from 1 out of 30,000 to 1 out 6,000 newborns [ 1 - 3 ] and representing about one third/one fourth of the total incidence of the congenital upper limb anomalies [ 4 - 6 ]. The RDs explain the vast majority of the malformations of the radial side of the arm, whereas the frequency of other defects, i.e.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations